Participation of Adrenal and Cholinergic Brain Systems in Regulation of Neurocytes Activity of Hypothalamus and Adenohypophysis Thyrotropocytes in Birds under EffÐµct of Chronic Cold Stress - Oleksiyenko, N. V.; Pazyuk, L. M.; Buzinska, N. O.; Dzerzhinsky, M. E. (Problems of Cryobiology and Cryomedicine, 2004)
Choline- and adrenergic brain systems are found to be involved into the adaptation reaction of hypothalamo-pituitary-thyroid system in birds on a long-term cooling due to the stimulating effect.